PENGUKURAN KINERJA PERUSAHAAN DENGAN PENDEKATAN BALANCED SCORECARD PADA PT. CIPTA GRIYA DINAMIKA - Selvi Yohana; Makhdalena Makhdalena; Gusnardi Gusnardi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACT : This research was done in Developer Company of PT. Cipta Griya Dinamika, by using Balanced Scorecard Approach with four perpectives which measured, which are the financial perpective, customer perpective, internal business process perspective and growth and study perpective. Research method which used in analyse descriptive, history analyse and survey. Data analyse technique which used is using primary and secondary data. Research result that performance PT. Cipta Griya Dinamika for the financial perpectives, current ratio has averaged 151,63% is categorized as not good because less than 200%, profit margin is categorized as good, operating ratio is categorized as good and ROI is categorized as good. For the customer perpectives, achievement customer is categorized as not good because less than last year, retention customer is categorized as good, profitability customer is categorized as good and satisfaction customer is in the good criteria because the 53 than 67 customers or 79,10% were satisfied for PT. Cipta Griya Dinamika. Internal business process perspective is nothing because PT. Cipta Griya Dinamika not make innovation process and on sale service, so that is categorized as not good. Growth and study perpective, employees productifity is categorized as good, employees retention is categorized as good and employees satisfaction is in the good criteria because the 4 than 7 employees or 57,14% were very satisfied for PT. Cipta Griya DinamikaKeyword : Performance, balanced scorecard